Haloperidol for the treatment of opioid addiction in advanced cancer patients: a case series. Issue 2 (17th February 2020) - Parisi, Alessandro; Pensieri, Maria Vittoria; Cortellini, Alessio; D'Orazio, Carla; Ficorella, Corrado; Verna, Lucilla; Porzio, Giampiero
Abstract: Opioid addiction, if not well diagnosed and treated, can be a significant challenge for optimal pain management even in cancer patients. To date there is no definitive pharmacological standard of care for treating addiction, especially in this setting of patients. We present a clinical case series of three opioid-addicted advanced cancer patients, effectively treated with haloperidol, a well-known first-generation typical antipsychotic.